Operation research the influence of venture capital on the growth of e-commerce listed enterprises - Perumal, Thinagaran; Allur, Naga Sushma; Devi, Durga Praveen; Dondapati, Koteeswarao; Himabindu, .; Kodadi, Sharadha (World Scientific Publishing, 2024)
Venture capital is essential to the growth of small and medium enterprises (SMEs) in developed e-commerce countries. SMEs play a crucial role in the economic development of both developing and developed countries. This paper proposes the influence of venture capital on the growth of e-commerce in small and medium enterprises using the propensity score matching (PSM) method. PSM is defined as the statistical analysis of observational data, where a statistical matching method attempts to evaluate the impacts of a treatment or policy. The experimental results show that the effect of e-commerce on SMEs who received venture capital financing experience improves the performance of employment growth and sales. Our findings reveal that VC significantly enhances employment rates and sales performance in e-commerce sectors. The study underscores the critical role of venture capital in driving innovation and growth within SMEs, providing valuable insights for investors and policymakers aiming to foster economic development.